2005
DOI: 10.1007/s10308-005-0037-z
|View full text |Cite
|
Sign up to set email alerts
|

A note on the feasibility of a monetary area in the East Asia

Abstract: After the constitution of the European Monetary Union (EMU), a new scope for monetary coordination is emerging in other regional areas. The standard approach to theoretically analyse the feasibility of a monetary union is the optimum currency areas (OCA) approach. Although this approach has been claimed to be non-operative, recent studies using synchronisation measures have shown a high potential applicability. This paper provides an empirical application of the OCA theory to a hypothetical East Asian monetary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Quite the opposite, some authors such as Wilson and Choy (2007) have demonstrated that East Asian countries are structurally too different to constitute a monetary union. In the same vein, using Japan as the reference country, Font-Vilalta and Costa-Font (2006) found that despite increasing synchronization of macroeconomic determinants of a monetary area, the outlook of an Asian currency union is still not feasible. Though their results differ, the standard framework of analysis used hinges on the theory of optimum currency areas (OCA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite the opposite, some authors such as Wilson and Choy (2007) have demonstrated that East Asian countries are structurally too different to constitute a monetary union. In the same vein, using Japan as the reference country, Font-Vilalta and Costa-Font (2006) found that despite increasing synchronization of macroeconomic determinants of a monetary area, the outlook of an Asian currency union is still not feasible. Though their results differ, the standard framework of analysis used hinges on the theory of optimum currency areas (OCA).…”
Section: Introductionmentioning
confidence: 99%
“…A total of ten dimensions are explored in which the first five items are measured relative to a reference country, a prospective monetary anchor country for East Asia, whilst the remaining five facets are measured in absolute terms. Unlike Font-Vilalta and Costa-Font (2006) who utilized only Japan as the reference country, three alternative reference counries, namely the US, Japan, and China are considered here. In some ways, the exercise does signify the relative economic dominance of the three largest economies to the region.…”
Section: Introductionmentioning
confidence: 99%